The place of e-learning in special education (2010)
The traditional pedagogical methods of teaching have promoted rote learning among children where the traditional learner is a passive recipient of whatever is being taught. Today, there is the challenge of integrating e-leaming at all levels of education. However, exceptional children who have different types of impairments have not benefited immensely like their able-bodied mates and those in developed nations like USA and Europe. This paper, however investigates the place of e-leaming in special education, the supporting theory, as well as e-leaming solutions for teaching children with special needs and customizing e-leaming for both students and teachers. The study used 19 female participants with different spans of work experience, and found out that they possess positive dispositions towards e-leaming in the educating children with special education needs.